Tensões e contradições na implementação do Proeja : hegemonia e contra-hegemonia no contexto do projeto neoliberal e neodesenvolvimentista - Silva, Miguel Vinicius Teixeira da (2016)
This work sends to a study about the implementation and institucionalização of the PROEJA in the Federal Institute of the Holy Spirit. In this sense, search problematizar the tensions and contradictions that wrap the process of creation and implementation of the PROEJA in the federal net, having in mind the paper of the State in the schooling offer and of profissionalização. The inquiry analyses the origin of the program in the government Squid and his continuity in the government Dilma. For so much, the analysis is, especially politics, having in mind the project neoliberal and neodesenvolvimentista. With the intention of proposing a discussion of the object on basis of the Dialectic Historical Materialism, one understands himself what in the heart of the theme are countless contradictions when capital was based on the dialectic relation x I work. In this form, it carries out a discussion of the PROEJA in his historicidade in the IFES, taking his legal base as a starting point. The proposal metodológica is of qualitative nature, taking the Dialectic Historical Materialism as a beginning norteador, aiming at a Marxist perception of the problem. So, one chooses by three analysis ways: in the initial form, the analysis of the institutional documentation of the program that includes the legal landmark and documents relative to his implementation. The second way sends to a bibliographical inquiry of the recent works carried out about the theme. In the third way the going to field happens interviews in depth with the subjects and gestores of the PROEJA. The results point to a program that is while it forces - hegemônica in the Federal Institute of the Holy Spirit, having in mind the tradition of the work in his school culture it is characterized for practical selective meritocráticas and not included. This context thinks straightly about the school offer revealing of tensions and contradictions the PROEJA.